Influence of the detergent formulation on the concentration of phosphorus in the sewage inflows to the WWTPs: the Brazilian experience. Issue 10 (19th May 2018) - Quevedo, Claudia Maria Gomes de; Piveli, Roque Passos; Paganini, Wanderley da Silva
ABSTRACT: This work seeks to discuss the presence of phosphorus in raw sewage considering the formulation of the powder detergent for cleaning fabrics currently sold in Brazil. Based on the results of laboratory analyses performed in the sewage inflows to three wastewater treatment plants (WWTPs) located in São Paulo state, it evaluates the different fractions of this element and sizes the impact caused by the product. The average concentration of total phosphorus (total-P) in sewage inflows has shown a reduction trend over the years, and it is currently between 5.3 and 7.6 mg/L. The participation of organic phosphorus (org-P) tends to be higher than that of the inorganic phosphorus (inorg-P) with average around 64% of total-P. This situation indicates a change from the default and it may be influenced by the reduced contribution of phosphorus in the powder detergents. It was concluded that the formulation of the Brazilian products, which have a very low phosphate content, less than 0.01% by weight, may have altered the phosphorus dynamics in sewage. In other respects, results have shown the need to enhance actions aimed at controlling the sources of phosphorus in sewage, with a view to assure preventive measures to water pollution processes.